Method of preparation of silver nanoparticles - Radu, Son; Loo, Yuet Ying; Chieng, Buong Woei (2012)
The invention relates to a method of synthesis of silver nanoparticles, which comprises the step of reducing a solution of water-soluble silver salt using a herbal extract. It also relates to the resulting silver nanoparticles having an average particle size of less than 5 nm.